2005
DOI: 10.1159/000085297
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA19-9 Measurement Increases the Effectiveness of Staging Laparoscopy in Patients with Suspected Pancreatic Malignancy

Abstract: Background/Aims: Staging laparoscopy for suspected pancreatic neoplasia is not widely accepted due to its low yield. The aim of this study was to determine if serum carbohydrate antigen (CA19-9) levels could be used to improve the selection of patients for staging laparoscopy. Methods: The data from a prospectively collected database (1997–2004) with 159 patients who had computed tomography-predicted resectable disease and who had undergone laparoscopic staging were analysed to determine if a low preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 42 publications
(44 reference statements)
1
25
0
1
Order By: Relevance
“…Adopting a level of >150 kU/l targets a patient population for whom the diagnostic yield from staging laparoscopy is maximised in terms of detecting occult metastatic disease [9]. One study demonstrated marked variability in the pattern of CA19-9 change following preoperative resolution of obstructive jaundice in cases of pancreatic adenocarcinoma, with levels falling in some cases and increasing in others [10].…”
Section: Introductionmentioning
confidence: 99%
“…Adopting a level of >150 kU/l targets a patient population for whom the diagnostic yield from staging laparoscopy is maximised in terms of detecting occult metastatic disease [9]. One study demonstrated marked variability in the pattern of CA19-9 change following preoperative resolution of obstructive jaundice in cases of pancreatic adenocarcinoma, with levels falling in some cases and increasing in others [10].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] A cancer antigen 19-9 level of 215 U/ml was proposed to select high-risk patients. 24 If this cutoff point would have been applied to the current series, about half of the patients with distant metastases would unfairly be excluded for SL (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated that laparoscopy is both safe and feasible to better assess resectability in pancreatic cancer patients before resorting to an open resective procedure, especially when associated with laparoscopic ultrasound [12,13,14,15,16,17,18]. Moreover, other authors have reported that such an approach can be adopted on a routine basis [19,20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The role of laparoscopy and laparoscopic US in staging pancreatic cancer is well established [12,13,14,15,16,17,18], and the procedure is considered routine before exploratory laparotomy for pancreatic resection by several high-volume centers [19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%